THE IMPACT OF INTERACTIVE METHODS ON ONLINE DIDACTIC ACTIVITIES - Enachi-Vasluianu, Luiza; Mălureanu, Flavia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
The period of online didactic activities, caused by Sars-CoV-2 pandemic, offered teachers and students the opportunity to focus more on what is essential, on the elements with qualitative impact, on abilities and skills, rather than on content and peripheral elements (Botnariuc & Cucoș, 2020). From this perspective, the use of interactive methods in teaching and in solving cooperative learning assignments was one of the strategies used by teachers to maintain interest in learning, to strengthen the teaching process and to promote intellectual, verbal, social and emotional exchanges among students.Our study focuses on the opinions of teachers from primary and lower secondary schools regarding the impact, the effectiveness of interactive methods in online didactic activities. The study involved focus group discussions and the selection of the most often used interactive methods (clustering technique, quadrants, conceptual maps, starbursting, brainstorming, quintet, think-pair-share, lotus blossom technique etc.) to be transposed into items in the questionnaire used in the research. The information gathered was interpreted using the SPSS analysis. The results of the study provide a data base and a possible framework to facilitate eLearning and a possible working strategy for primary and lower secondary school teachers to ensure students effective interactive learning experiences.